Pengaruh Kebijakan Dividen, Investasi, dan Hutang Terhadap Nilai Perusahaan - Alexander Wahyu Eka Putra; Yusni Warastuti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The evaluation of companies in Indonesia, particularly in the manufacturing sector, which drives the economy, is influenced by various elements. The study analyzed the impact of three main factors on firm valuation: dividend policy, investment decisions, and debt policy. Population in the study includes all manufacturing business entities listed on the Indonesia Stock Exchange from 2019-2022. The sample of 291 companies was chosen through purposive sampling with specific criteria. Research findings indicate that investment decisions have a significant positive impact on firm value, dividend policy and debt policy do not have a significant effect.